On the sets of branch points of mappings more general than quasiregular - Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
It is shown that if a point x_0 ∊ ℝ^n, n ≥ 3, is an essential isolated singularity of an open discrete Q-mapping f : D → ℝ^n, B_f is the set of branch points of f in D; and a point z_0 ∊ ℝ^n is an asymptotic limit of f at the point x_0; then, for any neighborhood U containing the point x_0; the point z_0 ∊ f(B_f ∩ U) provided that the function Q has either a finite mean oscillation at the point x_0 or a logarithmic singularity whose order does not exceed n − 1: Moreover, for n ≥ 2; under the indicated conditions imposed on the function Q; every point of the set ℝ^n f(D) is an asymptotic limit of f at the point x_0. For n ≥ 3, the following relation is true: ℝ^n∖f(D) ⊂f(B_f ∩ U). In addition, if ∞ ∉ f(D), then the set f B_f is infinite and x_0 ∈ B_f.